TOSLS Cognitive Instrument to Measure Students' Scientific Literacy Abilities - Maulidatul Kurnia Pratiwi; Sunu Kuntjoro; Titin Sunarti; Mohammad Budiyanto (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research is for the development of the TOSLS scientific literacy assessment instrument to determine the scientific literacy abilities of undergraduate science education students. Scientific literacy skills need to be known as a form of evaluation in learning. Scientific literacy skills are one of the abilities students must have after graduating from college and facing the work environment. Method: The quantitative method used in this research uses a Rasch model approach from 29 Bachelor of Science Education program students. Indicators of item suitability with Rasch model analysis measure this quality. The questions consist of 9 multiple choice questions with a correct score of 1 and an incorrect score of 0. Data processing uses MS Excel and SPSS 25 software. Results: The results show that all fit items, according to Rasch analysis, can be maintained without revision and used as a question instrument to measure the level of science literacy ability science for students with moderate scientific literacy abilities. Novelty: The research contribution of this question instrument can be used as reference material for evaluating the lecture process in biophysics courses on fermentation topics based on the level of scientific literacy ability.